Nerve sparing feminizing genitoplasty with corporal septum excision in non-classic congenital adrenal hyperplasia - Elçi Atılgan, Adeviye; Kılıç, Fatma; Acar, Ali; Akçaoğlu, Tuğba; Uzun, Asiye (Journal of Surgery and Medicine, 2021)
Background/Aim: Non-classic congenital adrenal hyperplasia (CAH) is a milder form of CAH. The CYP21A2 gene is involved in the etiopathogenesis of both severe (classic) and mild (non-classic) form CAH, however, genetic mutations in non-classic CAH result in less impairment of 21-hydroxylase activity. Therefore, as in classic CAH, patients with non-classical CAH have no signs and symptoms of cortisol deficiency. Instead, there may be signs of hyperandrogenism that can appear later in childhood or in early adulthood. Due to excess androgenic effect on clitoris, labia minora, majora and the vagina, feminizing genitoplasty should be performed to make gender identities consistent and reshape the proper genital anatomy for sexual intercourse. However, there are few studies and controversy on feminizing genitoplasty procedures in adulthood. In this study, we aimed to design a new procedure to spare the nerves of the clitoris as well as the clitoral body, along with the cavernous tissue. Methods: This is a case series of nine patients with a mean age of 24.8 years diagnosed with non-classic CAH who underwent feminizing genitoplasty, in which nerve-sparing clitoroplasty was performed with corporal septum excision by ventral approach. Initially, diagnostic cystoscopy was performed to detect the level of vaginal confluence into the urogenital sinus. The enlarged clitoris was degloved from 10 mm proximal to the glans up to the symphysis pubis. Corporal septum was excised from the ventral part of the clitoris up to the bifurcation of crura. Neurovascular bundle was preserved completely dorsally, and the clitoris was folded over itself and fixed at the level of crural bifurcation at 3 and 9 o'clock positions. Degloved clitoral preputium was used as Byars’ flaps for labiaplasty. A perineal inverted U incision was made and the vaginal introitus was enlarged with this flap. Female Genital Image Scale (FGIS) was used in the assessment of patients’ postoperative genital self-image. Results: Feminizing genitoplasty (nerve-sparing clitoroplasty with corporal septum excision, labiaplasty and perineal flap vaginoplasty) was performed in nine patients diagnosed with non-classic CAH. The mean operation time was 112 minutes with a range of 90-140 minutes. Urogenital sinus mobilization was not performed as the vaginal confluence into urogenital sinus was low in cystoscopy. Patients were re-assessed at 1 month, 3 months and 6 months postoperatively. FGIS scores showed that four patients were “very satisfied,” one patient was “satisfied,” 2 patients were “moderately satisfied”, and one patient was “dissatisfied.” The maximum follow up was 2 years with no recorded short or long-term complications. Conclusion: Nerve sparing clitoroplasty with corporal septum excision is a good option with satisfactory long term results for non-classic CAH patients. However, we need many more comparative studies to decide the gold standard method for optimal physiologic and cosmetic outcomes in CAH patients.